Anti-mitochondrial Tryparedoxin Peroxidase Monoclonal Antibody-Based Immunohistochemistry for Diagnosis of Cutaneous Leishmaniasis - Freire, Mariana Lourenço; Rego, Felipe Dutra; Lopes, Karine Ferreira; Coutinho, Lucélia Antunes; Grenfell, Rafaella Fortini Queiroz; Avelar, Daniel Moreira; Cota, Gláucia; Pascoal-Xavier, Marcelo Antônio; Oliveira, Edward (Frontiers in Microbiology, 2022)
Cutaneous leishmaniasis (CL) remains a globally spreading public health problem. Among Latin America countries, Brazil has the greatest number of recorded CL cases with several Leishmania species being associated with human cases. Laboratory diagnosis is one of the major challenges to disease control due to the low accuracy of parasitological techniques, the restricted use of molecular techniques, and the importance of differential diagnosis with regard to several dermatological and systemic diseases. In response, we have developed and validated an immunohistochemistry (IHC) technique for CL diagnosis using anti-mTXNPx monoclonal antibody (mAb). Recombinant Leishmania–mTXNPx was produced and used as an immunogen for mAb production through the somatic hybridization technique. The viability of mAb labeling of Leishmania amastigotes was tested by IHC performed with skin biopsies from hamsters experimentally infected with Leishmania amazonensis, Leishmania braziliensis, and Leishmania guyanensis. The enzymes horseradish peroxidase (IHC-HRP) and alkaline phosphatase (IHC-AP), both biotin-free polymer detection systems, were used in the standardization step. The IHC was further validated with skin biopsies from 49 CL patients diagnosed by clinical examination and quantitative real-time polymerase chain reaction and from 37 patients presenting other dermatological infectious diseases. Other parasitological techniques, such as direct examination and culture, were also performed for confirmed CL patients. Histopathology and IHC were performed for all included patients. Overall, the highest sensitivity was observed for IHC-AP (85.7%), followed by IHC-HRP (79.6%), direct examination (77.6%), histopathological examination (HE; 65.3%), and in vitro culture (49%). Only IHC and HE presented specificity over 90% and were able to detect CL patients regardless of parasite burden (odds ratio > 1.94; 95%CI: 0.34–11.23). A significant increase in positivity rates was observed when IHC-AP was combined with direct examination (95.9%) and HE (93.9%). The IHC techniques evaluated in here detected the main Leishmania species causing CL in Brazil and can support diagnostic strategies for controlling this neglected disease, especially if used in combination with other approaches for an integrative laboratorial diagnosis.